(untitled) (Revista de Psicología, 2019)
The multidimensional approach of marital satisfaction includes three dimensions: context, individual and interaction, all of which explain couple relationships. In this paper the elements of each dimension are reanalyzed. In order to achieve this aim, 131 participants from Mexico City answered 3 open-ended questions; these revealed that financial situation, respect, time and shared activities, sense of humor, and personality are the most important elements that influence marital satisfaction.